Population-based assessment of relationship between volume of practice and outcomes in head and neck cancer patients treated in a provincially coordinated radiotherapy program. Issue 1 (July 2017) - McLay, Mary; Stedford, Adrienne; Yurkowski, Emily; Matlock, Scott; Cheung, Winson; Tran, Eric; Berthelet, Eric; Wu, Jonn; Olson, Robert
Abstract: Background and purpose: Literature suggests that higher volumes of practice are associated with better survival outcomes for head and neck cancer (HNC) patients. The objective of this study was to evaluate the effect of treatment center on the overall survival (OS) and cancer-specific survival (CSS) in a provincially coordinated program. Materials and methods: A population-based provincial database was used to identify all patients in BC diagnosed for the first time with a primary non-thyroid HNC and treated with radiotherapy between 2006 and 2011. Results: 2330 HNC patients were included. On multivariable analysis, after controlling for age, gender, cancer stage, anatomical site, treatment and physician case frequency, OS (HR range = 0.91–1.05; p = 0.60–0.88) did not significantly differ by center. OS was also not significantly different for patients treated by physicians with low case frequency (HR = 0.96; 0.81–1.13; p = 0.60) and medium case frequency (HR = 1.12; 0.84–1.49; p = 0.43) in reference to high case frequency. There was no effect on OS or head and neck CSS when physician case frequency was treated as a continuous variable. Conclusions: In our provincially coordinated radiotherapy program, there was no significant difference in survival between cancer centers after controlling for differences in rurality, physician case volume and other potential confounding variables.